45 FKASA students turned nature lovers - Emma Melati, Burhanuddin (2018)
Forty-five students from Faculty of Civil Engineering & Earth Resources (FKASA) including foreign students joined forces in a noble act to conserve the environment by planting 500 mangrove tree saplings and cleaning up the shoreline of Chendor beach in Kuantan here on October 27, 2018.